Pemetaan Dampak Banjir Bandang terhadap Lahan Pertanian di Nagari Pauh Kamang Mudiak Kabupaten Agam - Anisa Fatihah; Hendry Frananda (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The objectives of the study are: 1) To analyze the level of vulnerability of agricultural land to flash floods in Nagari Pauh Kamang Mudiak, 2) To analyze the condition of agricultural land in Nagari Pauh Kamang Mudiak before and after the flash flood. The results of this study: 1) Analysis of the level of vulnerability of agricultural land to flash floods in Nagari Pauh Kamang Mudiak, namely in the safe class covering an area of 8.34 hectares, the non-vulnerable class covering an area of 12.01 hectares, the vulnerable class covering an area of 51.91 hectares and the very vulnerable class covering an area of 18.13 hectares. This shows that most of the research areas have a high level of vulnerability to flash floods. Furthermore, the analysis of flash flood risks with 4 risk classifications is an area with a low risk of 16.94 hectares, a moderate area of 30.60 hectares, a high area of 37.78 hectares, and a very high area of 5.07 hectares. Based on the results of this analysis, the agricultural land most affected by the flash flood in Nagari Pauh Kamang Mudiak is rice fields covering an area of 72.2 hectares, 2) Analysis of the condition of agricultural land vegetation in Nagari Pauh Kamang Mudiak before and after the flash flood, namely with 5 classes, namely the very low greenness class covering an area of 12.69 hectares, low covering an area of 29.69 hectares, medium covering an area of 13.22 hectares, and high covering an area of 34.84 hectares. The results of the accuracy test using overall accuracy reached a suitability of 89.58% and the kappa coefficient reached a suitability of 84.32%, meaning good accuracysuitability between the classification results and actual conditions in the field.